Проблема Іншого в контексті формування сучасної національної ідентичності - Наконечний, М. В.; Nakonechnyi, M. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено національну ідентичність у її тісному зв’язку із соціальною реальністю, що трансфор-мується під впливом глобалізації. Особливу увагу звернуто на проблему Іншого як невід’ємного складника, що впливає на формування сучасної національної ідентичності. The article examines the national identity in its close association with social reality, personal and collective consciousness that is transforming under the influence of globalization. Singled out the impact of the revaluation, rethinking and critique of traditional values and moral-ethical ideals on a specificity of modern identification processes. Particular attention is paid to the problem of «Other» as an integral component that affects the formation of a modern national identity. National identity is understood as a special kind of identity with complex multi-level structure, which has its typology, principles of formation, applies to individual and collective consciousness and includes specific models, parameters, rules and principles that are the basis of national identification. Simultaneously, the problem of the «Other» is an integral part of national identity, which allows to define the selfness and the difference of the nation from its «Other».
The Problem of the «Other» in the Context of the Formation of a Modern National Identity
Keywords: ідентичність; identity; ідентифікація; identification; національна ідентичність; national identity; Інший; the «Other»; глобалізація; globalization; глобалізаційні трансформації; globalization transformations